Changes in carbon and nutrient fluxes from headwaters to ocean in a mountainous temperate to subtropical basin. Issue 13 (13th June 2017) - Mutema, Macdex; Chivenge, Pauline; Nivet, Fantine; Rabouille, Christophe; Thieu, Vincent; Chaplot, Vincent
Abstract: Water erosion provides major links in global cycles of carbon (C), nitrogen (N) and phosphorus (P). Although significant research on erosion mechanisms has been done, there is still little knowledge on C, N and P fluxes across landscapes to the ocean and their controlling factors in subtropical climates. A four‐year study quantifying and comparing particulate and dissolved C, N and P from multiple scales (microplot, plot, microcatchment, subcatchment, catchment, sub‐basin and basin) was performed in Thukela basin (≈30 000 km 2 ), South Africa. The basin climate was largely subtropical‐humid [mean annual precipitation (MAP) > 980 mm yr ‐1 ], but temperate (MAP >2000 mm yr ‐1 ) on the highlands. Open grassland, cropland and bushland were the major land uses. On average, 65, 24 and 4 g m ‐2 yr ‐1 C, N and P were displaced from original topsoil positions, but only 0.33, 0.005 and 0.002 mg m ‐2 yr ‐1 were, respectively, exported to the ocean. The fluxes decreased by 95, 97 and 84%, respectively, from plot to microcatchment outlet; and decreased further in downstream direction by >99% from microcatchment to basin outlet. The hillslope (microplot to microcatchment) fluxes correlated strongly with rainfall parameters. Particulate contributions dominated hillslope fluxes at 73, 81 and 76% of total annual C, N and P, respectively. Although particulate C dominated in the microcatchment‐catchment reach (55%), N (54%) and P (69%) were dominated by dissolved forms. The lower basin zone was dominated by dissolved flux contributions at 93, 81 and 78% for C, N and P for the sub‐basin outlet. These results suggested spatially varying drivers of C, N and P losses from the landscape to the ocean, via the river network. Deposition was envisaged the dominant hillslope level loss process, which gradually gave way to mineralization and biotic uptake in the river network as flux contributions shifted from being predominantly particulate to dissolved forms. Copyright © 2017 John Wiley & Sons, Ltd.